The occupational stress. On the Burnout Syndrome during the pandemic - Torres Cadillo, Rosa Isabel (2021)
The global crisis caused by the COVID-19 pandemic is an unprecedented event, in which all countries were forced to adopt different restrictive measures to neutralize and slow the advance of the pandemic. Among these, we find remote work, telework, or work at home. This new work modality associated with confinement at home has forced workers to adapt to a new way of working. This scenario has led to the excessive growth of stress, known as (professional) burnout, i.e., the burned-out worker syndrome or burnout syndrome. This condition is an important public mental health problem since it represents a potential difficulty for both the employer and the worker.